Selective post-training time window for memory consolidation interference of cannabidiol into the prefrontal cortex: reduced dopaminergic modulation and immediate gene expression in limbic circuits - Rossignoli, Matheus Teixeira (2017)
The prefrontal cortex (PFC), amygdala and hippocampus display a coordinated activity during acquisition of associative fear memories. Evidence indicates that PFC engagement in aversive memory formation does not progress linearly as previously thought. Instead, it seems to be recruited at specific time windows after memory acquisition, which has implications for the treatment of posttraumatic stress disorders. Cannabidiol (CBD), the major non-psychotomimetic phytocannabinoid of the Cannabis sativa plant, is known to modulate contextual fear memory acquisition in rodents. However, it is still not clear how CBD interferes with PFC-dependent processes during post-training memory consolidation. Here, we tested whether intra-PFC infusions of CBD immediately after or 5 h following contextual fear conditioning was able to interfere with memory consolidation. Neurochemical and cellular correlates of the CBD treatment were evaluated by the quantification of extracellular levels of dopamine (DA), serotonin, and their metabolites in the PFC and by measuring the cellular expression of activity-dependent transcription factors in cortical and limbic regions. Our results indicate that bilateral intra-PFC CBD infusion impaired contextual fear memory consolidation when applied 5 h after conditioning, but had no effect when applied immediately after it. This effect was associated with a reduction in DA turnover in the PFC following retrieval 5 days after training. We also observed that post-conditioning infusion of CBD reduced c-fos and zif-268 protein expression in the hippocampus, PFC, and thalamus. Our findings support that CBD interferes with contextual fear memory consolidation by reducing PFC influence on cortico-limbic circuits.